A first step in determining appropriate amounts of obstetric anesthesia work - Varaday Swarup S; Leighton Barbara L (BMC, 2012)
Abstract Ginosar, et al. describe a new performance indicator, the Obstetric Anesthesia Activity Index, to represent the current amount of obstetric anesthesia work done daily at each of 25 Israeli hospitals. The authors claim, correctly, that this index is a closer reflection of the anesthetic workload than simply looking at the number of deliveries at each hospital. However, the Obstetric Anesthesia Activity Index could easily be refined to reflect more closely the actual obstetric anesthesia workload by using the average cesarean delivery time for each hospital rather than one value for all hospitals. Although the authors state that they developed the Obstetric Anesthesia Activity Index out of concern for inadequate obstetric anesthesia manpower in Israel, they have not compared the Obstetric Anesthesia Activity Index with the size of the patient population or any measure of patient satisfaction or patient safety. In its current form, the Obstetric Anesthesia Activity Index describes the current work situation but does not evaluate the extent of the unmet need for additional anesthesia providers. Despite these shortcomings, the Obstetric Anesthesia Activity Index is an important first step in developing a tool to assess unmet obstetric anesthesia needs.